Vertical Price Control and Parallel Imports : Theory and Evidence - Maskus, Keith E. (World Bank, Washington, DC, 2015)
A policy of national exhaustion says that the rights to control distribution, end upon first sale only within a country, thereby permitting rights holders to exclude parallel imports. A policy of international exhaustion states that such rights end upon first sale anywhere, and therefore permits parallel imports. The European Union has a policy of regional exhaustion within its territory. Language in the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) suggests that this policy choice remains the prerogative of individual countries. The authors review the international policy debate about parallel imports, which are controversial because they erode the ability of intellectual property owners to segment markets. Against considerable opposition, for example, Australia recently deregulated its import controls in major copyrighted goods, because domestic prices were evidently sustained at high levels by those controls. Both the European Union, and the United States are considering permitting parallel imports of prescription pharmaceuticals from abroad. Developing countries must consider their exhaustion regimes in the context of competition policies, and intellectual property rights. Economic theory demonstrates that the welfare tradeoffs in regulating parallel imports, are complex and depend on circumstances. The authors advance a new model that analyzes parallel imports as a response to vertical pricing arrangements between a rights holder ("manufacturer") and a foreign distributor. In this model, if markets were segmented, the manufacturer would change a wholesale price to its foreign distributor to ensure an efficient (profit-maximizing) retail price. But if markets were integrated by parallel trade, the distributor could purchase the good at a wholesale price, and sell it back to the manufacturer's home market at the local retail price. If transport costs were low enough, this would be profitable, but would diminish the return to the manufacturer, and waste resources in costly trade. So there would be tradeoffs: Parallel imports would benefit consumers in the high-price country, but hurt consumers in the low-price country. Such trade forces the manufacturer to set an inefficient wholesale price to limit its extent; it also consumes resources. The welfare implications of allowing parallel imports are ambiguous. If the costs of engaging in such trade were low, there would be gains from permitting it; if the costs were high, it would be more sensible to ban it. Countries near each other, with low trade barriers, might prefer an open regime of parallel trade. The vertical pricing model provides an explanation of this pricing behavior that is consistent with manufacturer's preferences to deter parallel trade.